Campus Canopy, 1943-02-19 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1943)
Exam Schedule -- Don't Let Your Hair-Do Stop You From Joining The WAACS -- Library Displays Georgia Exhibit -- Victory Book Drive Is Now Underway On The Campus -- Cupid Scoops All Others On His February 14 Visit to GSWC
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals